Microbial contamination and quantitative microbial risk assessment of high-density polyethylene (HDPE) film sachet drinking water in Ghana. (19th October 2022) - Angnunavuri, Prosper Naah; Attiogbe, Francis; Mensah, Bismark
Abstract: The present research estimated the impact of storage on the microbial quality of high-density polyethylene drinking water. Samples were taken from two popular companies in Greater Accra using a two-sided exact test in SAS JMP to estimate the sample size. The samples were stored across three temperature profiles at 8 °C, 30 °C (average room temperature), and 40 °C (average outdoor temperature) for 28 days. The samples were examined using standard microbiological methods for heterotrophic plate counts (HPCs), faecal coliforms, and Escherichia coli . The data were described and regressed with Microsoft Excel, Argo 4.3.1, and SAS JMP software. The results demonstrated increasing deterioration of the water samples for all microbial indices at all temperatures with increasing storage duration. The highest HPC, faecal coliforms, and E. coli were 1, 312; 622; and 252 cfu/100 mL, respectively, all at 40 °C. The daily risk of infection due to E. coli O157:H7 was 5.22 × 10 −5 infections per child per day for children under 5 years, and 1.6 × 10 −4 attacks per adult per day, compared to the upper limit of 1.0 × 10 −6 . These results are higher than recommended exposures, and interventions along the sachet drinking water value chain are needed to protect public health. HIGHLIGHTS: Sachet water contributes to water security in Ghana. HPC, faecal coliforms, and Escherichia coli were 1, 312; 622; and 252 cfu/100 mL, respectively. The mean daily morbidity was between 5.33 × 10 −5 and 2.36 × 10 −2 infections per person per day. Daily and annual rates of infections were higher than the recommended limit of 1 × 10 −6 . Between 22, 700 and 30, 189 children under 5 stood the risk of enteric infections from E. coli O157:H7. Graphical Abstract